How sex puts you in gendered shoes sexuality-priming leads to gender-based self-perception and behavior. [article]. - Hundhammer, Tanja
Scripts for sexual behavior dictate that women be submissive and tender and that men be assertive and dominant, reflecting the stereotype view of women as communal and of men as agentic. Six experiments tested the hypothesis that exposure to sexuality cues causes men's and women's momentary self-perceptions and concomitant behavior to become more gender-typical. Using both pictorial and verbal prime materials that were presented both supraliminally and subliminally, we found that sex-priming strengthened gender-based self-perceptions (i.e., faster self-categorization as a woman or man; Study 1), heightened identification with one's own gender (Study 2), increased gender self-stereotyping (Study 3), and elicited greater submissiveness in women's behavior and greater assertiveness in men's behavior (Studies 4 and 5). These findings indicate that sex-priming causes self-perception and social behavior to become "attuned" to gender role primes. The potentially detrimental effects of sex-priming and possible countermeasures are discussed. -(from the authors)